Soft tissue sarcomas of the buttock: A systematic review and meta-analysis. (December 2022) - Sacco, Riccardo; Lalevée, Matthieu; Pellegrino, Pietro; Ferro, Andrea; Yasmine, Bendoukha; André, Gillibert; Matthieu, Gilleron; Hamza, Amine; Piana, Raimondo; Dujardin, Franck
Abstract: Background: Soft tissue sarcomas of the buttock (BSTS) are historically associated with a poor prognosis. The literature includes retrospective studies with small sample size. It is difficult to estimate the rate of local recurrence (LR), distant metastasis (DM) and overall survival (OS). A systematic review and meta-analysis was deployed to summarize the available information on BSTS patients that underwent surgical treatment. Methods: The PubMed, EMBASE, Scopus and Google Scholar databases were reviewed for eligible studies following PRISMA guidelines. Inclusion criteria: (1) primary BSTS confirmed by pathological biopsy (2) indication for surgical treatment (3) reporting either the rate of LR, DM, or OS at 5-year (4) articles published up to December 2021 (5) english language. The Methodological Index for Non-Randomized Studies (MINORS) was applied for the quality appraisal. Results: Six eligible studies with 216 BSTS patients were identified. Most patients underwent surgical resection, associated with radiation therapy. The most represented histological types were liposarcoma (n = 43, 19, 9%), rhabdomyosarcoma (n = 27, 12.5%), and undifferentiated pleomorphic sarcoma (n = 23, 10.6%). High-grade tumor rates ranged from 37% to 88.2%, marginal resection rates from 20.3% to 50%, LR rates from 0% to 62.5%, DM rates from 37.5% to 62.5%. The pooled 5-year OS from 1941 to 2002 was 41% (IC95%: 33%–49%). The average MINORS score was 9.3 (range: 6 to 11). Conclusions: Surgical resection of BSTS had on average dissatisfactory outcomes, and the 5-year overall survival was poor, with high rates of local recurrence and distant metastasis. An effort to collect new data with a higher level of evidence is warranted. Highlights: Soft tissue sarcoma of the buttock are historically associated with a poor prognosis. A systematic review and meta-analysis were conducted to assess the available information in the literature. The 5-year overall survival from 1941 to 2002 was poor, with high rates of local recurrence and distant metastasis. An effort to collect new data with a higher level of evidence is warranted.